Contemporary reinventions of Chinese calligraphy. A semiotic exploration - Giacomo Festi; Weihuan Hou (Ocula)
Chinese calligraphy can be semiotically approached from its contemporary transformations, in an historical moment of cultural revival and media popularity. After an initial dialogue with recent contributions about the peculiarities of that long lasting tradition, where the sensori-motor dimension of the calligraphic practice will be considered, the contribution will delve into an analytical observation of four contemporary artists, all of them reinventing calligraphy in their own terms. The semiotic analysis will move in between the visible plastic features, the universes of meanings evoked and the way the practice itself is assumed by the artists. Wang Dongling, Xu Bing, Lui Shou Kwan, Wang Tiande will be the authors of a semiotic test. Can we finally map the forms of alteration of the calligraphy? The practice itself is considered as embedding an entire form of life, culturally attached to the values of Daoism or Confucianism and the final proposed mapping is grasping the alterations of that form of life.